1998
DOI: 10.23986/afsci.5616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anionic salts in concentrate mixture and calcium intake on some blood and urine minerals, acid-base balance and feed intake of dry pregnant cows on grass silage based feeding

Abstract: Twelve Ayrshire and eight Friesian cows were randomly assigned to one of four prepartum diets in a 2 x 2 factorially designed experiment to determine the effect of anionic diet and calcium (Ca) intake on Ca metabolism, acid-base status and feed intake of grass silage based diets during the dry period. Four diets provided either 34 g or 74 g total dietary Ca/day, and were either anionic or cationic. Dietary cation-anion balance (DCAB), calculated as milliequivalents [(Na+ + K+) - (Cl- + S2-)], was -247 mEq/kg d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…The study done by [67] is not included in the calculations, as they did not include a group receiving feed with a negative DCAD. In 2 of the studies [73] and [107] the milk fever incidence was zero among cows in the positive as well as negative DCAD group (RR = 1). Excluding these results from the calculations, the RR changes from 0.35 to 0.19.…”
Section: Acidifying Rations (Dietary Cation-anion Difference Dcad)mentioning
confidence: 99%
See 3 more Smart Citations
“…The study done by [67] is not included in the calculations, as they did not include a group receiving feed with a negative DCAD. In 2 of the studies [73] and [107] the milk fever incidence was zero among cows in the positive as well as negative DCAD group (RR = 1). Excluding these results from the calculations, the RR changes from 0.35 to 0.19.…”
Section: Acidifying Rations (Dietary Cation-anion Difference Dcad)mentioning
confidence: 99%
“…vary considerably between the different studies. For instance some studies included cows of second or first parity [73,107,70], whereas others [10,79,67,41,8,36,37,39] only included "high risk" cows (≥ third parity). The interpretation of Fig.…”
Section: Acidifying Rations (Dietary Cation-anion Difference Dcad)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, Tucker et al (1991) found that udder oedema regressed postpartum more rapidly in cows previously fed a low DCAB (-30 mEq/kg DM) relative to cows fed a high DCAB (+90 mEq/kg DM). In an earlier study (Tauriainen et al, 1998a) severe udder oedema was unexpectedly observed in a high proportion of cows when the DCAB was -247 mEq/kg DM, but the incidence was not routinely evaluated and as such these findings were not documented.…”
Section: Introductionmentioning
confidence: 97%